Quick emotional intelligence activities for busy managers : 50 team exercises that get results in just 15 minutes - Lynn, Adele B. (AMACOM / American Management Association, 2007)
If you're managing a team, you know that emotional issues -- such as lack of trust and commitment, unresolved conflicts, and the inability of individuals to understand how their actions impact others -- can stop even the most promising groups from delivering great results. This book gives you powerful, proven exercises you can use to help you and your team. The book follows each activity with a discussion of its purpose, how to use it, and a list of post-activity questions to help solidify each lesson. Simple and easy-to-use, Quick Emotional Intelligence Activities for Busy Managers gives you the tools you need to get fast, powerful results from any team.